Ward committees and the management of development policy in Tshwane Metropolitan Municipality - Rabothata, Mogale Moses (My University, 2015)
The advent of democracy in 1994 and the local government reform process that followed heralded a new era of consultation with citizens on matters that affected them. One important aspect of this reform process is the introduction of the Ward committee system to foster public participation and subsequently the management of development policy. However, municipalities are increasingly challenged by service delivery protests. The challenge seems to be that Ward committees, having been established for the above purpose, have not been as effective as they should. A study in this regard was conducted amongst specific Ward committees in the Tshwane Metropolitan Municipality. The purpose of the study was to determine what inhibits Ward committees from playing their required role in respect of the management of development policy with particular reference to the abovementioned municipality. It was further intended to determine, although not comprehensively, some of the root causes of poor service delivery over and above bureaucratic incapacity. Seventy-six Ward committees of Tshwane Metropolitan Municipality before the current municipal realignment were categorized into two groups: those that experienced service delivery protests and those who did not. Following the categorization of Ward committees, one from each group was randomly selected to constitute units of analysis. A questionnaire was administered among the Ward committee members and interviews conducted with some ward councillors, including the Speaker. One of the findings is that the municipality has established Ward committees to ensure local community participation. This is despite participation being limited to compulsory consultation on issues of Integrated Development Plans and budgets. Another finding is that the municipality convenes a session immediately after the election of Ward committees to induct them into their roles and responsibilities. Despite this, ii the Ward committees are not adequately capacitated to discharge their mandate of, inter alia, making meaningful inputs on policy development, implementation, monitoring and evaluation. To address the above, it is essential that Ward committees are capacitated. This will include, but is not limited to, improving communication with those committees, allocating resources to them, promoting new or strengthening existing interest groups, acting upon issues raised by Ward committees, and developing and undertaking training programmes based on a training needs analysis.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits School of Governance, 2014.